In vitro anti-leishmanial effect of metallic meso-substituted porphyrin derivatives against Leishmania braziliensis and Leishmania panamensis promastigotes properties (2020)
In this study, a family of porphyrins based on 5,10,15,20-Tetrakis(4-ethylphenyl)porphyrin (1, Ph) and six metallo-derivatives (Zn2+(2, Ph-Zn), Sn4+(3, Ph-Sn), Mn2+ (4, Ph-Mn), Ni2+ (5, Ph-Ni), Al3+ (6, Ph-Al), and V3+ (7, Ph-V)) were tested as photosensitizers for photodynamic therapy against Leishmania braziliensis and panamensis. The singlet oxygen quantum yield value (FD) for (1–7) was measured using 1,3-diphenylisobenzofuran (DPBF) as a singlet oxygen trapping agent and 5,10,15,20-(tetraphenyl)-porphyrin (H2TPP) as a reference standard; besides, parasite viability was estimated by the MTT assay. After metal insertion into the porphyrin core, the FD increased from 0.76–0.90 and cell viability changed considerably. The FD and metal type changed the cytotoxic activity. Finally, (2) showed both the highest FD (0.90) and the best photodynamic activity against the parasites studied (IC50 of 1.2 M).